Exploration and Antimicrobial Activity Test of Secondary Metabolites from Endophytic Fungi of Curcuma Zedoaria from West Nusa Tenggara - Mario Mario; Sylvia Rizky Prima; Gian Primahana (Riviera Publishing, 2025)
Antibiotic resistance has become a significant public health issue in Indonesia, prompting the search for alternative antimicrobial agents from natural sources. Endophytic fungi symbiotically living inside medicinal plants such as Curcuma zedoaria (temu putih) have the potential to produce bioactive secondary metabolites that could serve as new antibacterial agents. This study aimed to isolate endophytic fungi from the rhizome of temu putih originating from West Nusa Tenggara (NTB), evaluate the antibacterial activity of isolates grown on Potato Dextrose Broth (PDB) and Yeast Malt Broth (YMB), and identify as well as elucidate the structure of the secondary metabolite compounds produced. This experimental comparative study involved isolation of endophytic fungi by surface sterilization, culturing on PDB and YMB media, extraction with ethyl acetate, and antibacterial testing against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 8739 using the microdilution method. Metabolite profiling was performed using HPLC-DAD, preparative HPLC for fractionation, LC-HRMS for molecular mass identification, and NMR spectroscopy for structural elucidation. Five endophytic fungal isolates were successfully obtained from the temu putih rhizome. Antibacterial activity was stronger in isolates cultured on PDB compared to YMB. From isolate TP 3 cultured in PDB, several secondary metabolite fractions were isolated, with fraction 4 (F4) containing linoleic acid as the pure compound. F4 demonstrated a Minimum Inhibitory Concentration (MIC) of 200 µg/mL against S. aureus, comparable to the TP 3 PDB isolate, while against E. coli, F4 showed MIC > 200 µg/mL and TP 3 PDB isolate showed an MIC of 100 µg/mL.